A Comparative Analysis on the Structure and Function of the Panax notoginseng Rhizosphere Microbiome - Kui, Ling; Chen, Baozheng; Chen, Jian; Sharifi, Rouhallah; Dong, Yang; Zhang, Zhanjiang; Miao, Jianhua (Frontiers in Microbiology, 2021)
Panax notoginseng, an important Chinese medicinal herb, can be mainly cultivated in two planting patterns, cropland planting (DT) and understory planting (LX). We speculate that the rhizosphere microbiome may vary in DT and LX and may play an important role in promoting the growth and health of P. notoginseng. In the present study, culture-independent Illumina HiSeq was employed to investigate the rhizosphere bacteria and fungi under DT and LX planting patterns. Predominant phyla include Proteobacteria, Acidobacteria, Actinobacteria, Gemmatimonadetes, and Ascomycota in the two planting patterns. DT has higher alpha diversity index than LX. The predominant LX-core genera include Bradyrhizobium, Streptomyces, and Actinomadura; and the predominant DT-core genera include Sphingomonas, Variovorax, and Novosphingobium. Total relative abundance of the disease-suppression phylum (Proteobacteria, Firmicutes, and Actinobacteria) and the potential plant growth-promoting rhizobacteria (PGPR) were both significantly higher in LX than in DT. We also identified over-presented microbial functional traits mediating plant-microbe and microbe-microbe interactions, nutrition acquisition, and plant-growth promotion in P. notoginseng rhizosphere. Our findings provide a valuable reference for studying beneficial microbes and pathogens of P. notoginseng planted in DT and LX.